1973
DOI: 10.1126/science.181.4101.753
|View full text |Cite
|
Sign up to set email alerts
|

Sanfilippo Disease Type B: Enzyme Replacement and Metabolic Correction in Cultured Fibroblasts

Abstract: alpha-Acetylglucosaminidase, purified from human placent, corrected the defect in mucopolysaccharide degradation when added to culture fibroblasts from patients with Sanfilippo disease type B. A small cellular concentration of enzyme gave a large corrective effect. The half-life of disappearance of enzyme activity was 4 to 7 days.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
1

Year Published

1974
1974
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(32 citation statements)
references
References 10 publications
0
31
0
1
Order By: Relevance
“…For the only therapeutic attempt reported for Sanfilippo B disease (16) no improvement was observed. Studies on the pinocytotic uptake and intracellular action of a-Nacetylglucosaminidase in cultured Sanfilippo B fibroblasts have been reported so far only for the enzyme from human urine (19) and placenta (20). Under the assumption that the serum enzyme has the same properties as the urinary enzyme with regard to pinocytosis and intracellular action it was calculated that per g cell protein, 80 ml of serum would be needed for half-maximal reduction of the accumulated mucopolysaccharides.…”
Section: Discussionmentioning
confidence: 99%
“…For the only therapeutic attempt reported for Sanfilippo B disease (16) no improvement was observed. Studies on the pinocytotic uptake and intracellular action of a-Nacetylglucosaminidase in cultured Sanfilippo B fibroblasts have been reported so far only for the enzyme from human urine (19) and placenta (20). Under the assumption that the serum enzyme has the same properties as the urinary enzyme with regard to pinocytosis and intracellular action it was calculated that per g cell protein, 80 ml of serum would be needed for half-maximal reduction of the accumulated mucopolysaccharides.…”
Section: Discussionmentioning
confidence: 99%
“…The changes in urinary glycosaminoglycans noted in these patients were transient, presumably because most lysosomal enzymes have relatively short halflives intracellularly (10)(11)(12). Studies on enzymes present in aimniotic fluid (13), leukocyte homogenates (14), anid serum (15), however, generally indicate a higher degree of stability.…”
Section: Introductionmentioning
confidence: 94%
“…Furthermore, in in vitro studies with cells from patients with mucopolysaccharidosis IIIB (Sanfilippo B disease) it has been shown that 2-5% of normal intracellular levels of enzyme would induce 42-70% correction of their abnormal glycosaminoglycan metabolism (10 …”
Section: +19mentioning
confidence: 99%
“…73 Early tissue culture experiments showed that exogenous enzymes could gain access to and degrade the accumulated intracellular substrates. 74,75 Even with achievement of 1-5% of normal cellular activity after supplying exogenous enzymes, these in vitro studies showed that storage substances dwindled. After these early exciting discoveries in 1970s, the progress in the 1980s was relatively slow.…”
Section: Screening and Testing For Imdsmentioning
confidence: 99%